รูปแบบการสืบทอดภูมิปัญญาท้องถิ่น ด้านการดูแลสุขภาพและการใช้ประโยชน์จากสมุนไพร - เฮงสุโข, เอกศักดิ์; มะณี, วิสิทธิ์ (วารสาร ศึกษาศาสตร์ มมร, 2018)
บทคัดย่อ           การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษารูปแบบการสืบทอดภูมิปัญญาท้องถิ่นด้านการดูแลสุขภาพและการใช้ประโยชน์จากสมุนไพร ประชากรที่ใช้ในการศึกษาครั้งนี้ คือ 1) กลุ่มชมรมแพทย์แผนไทยเภสัชพัฒนาภูมิปัญญาท้องถิ่น บ้านโนนศรีทอง หมู่ที่ 4 ตำบลโป่งเปือย อำเภอเมือง จังหวัดบึงกาฬ 2) กลุ่มผู้ปลูกแปรรูปสมุนไพรภูทอก บ้านคำแคนพัฒนา หมู่ที่ 6 ตำบลนาแสง อำเภอศรีวิไล จังหวัดบึงกาฬ และ 3) กลุ่มอนุรักษ์ภูมิปัญญาไทยบ้านสมุนไพร บ้านใหม่ชัยพร หมู่ที่ 11 ตำบลชัยพร อำเภอเมือง จังหวัดบึงกาฬ ใช้การสุ่มตัวอย่างอย่างง่าย (Simple random sampling) โดยคัดเลือกลุ่มตัวอย่างแบบเฉพาะเจาะจง ประกอบด้วย ปราชญ์ชาวบ้านด้านสมุนไพร หมอยาพื้นบ้าน หัวหน้ากลุ่มสมุนไพรทั้ง 3 กลุ่ม สมาชิกกลุ่มสมุนไพร และเครือญาติที่ได้รับการถ่ายทอดทางภูมิปัญญาในด้านสมุนไพร เก็บรวบรวมข้อมูลด้วยตนเอง โดยใช้รูปแบบการวิจัยเชิงคุณภาพ โดยเน้นการวิจัยแบบมีส่วนร่วม (Participatory Action Research : PAR) โดยใช้แบบสัมภาษณ์แบบมีโครงสร้าง ซึ่งผู้วิจัยได้นำเครื่องมือของ สุวรรณี  ไชยชนะ (2547)  มาปรับประยุกต์ใช้ในการวิจัยนี้ ผลการวิจัยพบว่า 1. รูปแบบการสืบทอดภูมิปัญญาท้องถิ่น ด้านการดูแลสุขภาพและการใช้ประโยชน์จากสมุนไพรของกลุ่มสมุนไพรจังหวัดบึงกาฬ เริ่มจาก 2 ลักษณะ คือ การได้รับการถ่ายทอดจากบุคคลในครอบครัว กับการได้รับการฝึกอบรมจากสถาบันทางการแพทย์ ซึ่งลักษณะแรก เป็นปัจจัยที่มีอิทธิพลต่อจำนวนผู้ประกอบอาชีพเกี่ยวกับสมุนไพรมากกว่า แต่ลักษณะหลังเป็นปัจจัยที่ส่งเสริมให้เกิดการยอมรับและความมั่นคงในอาชีพหมอสมุนไพร จึงพบว่า ไม่ว่าจะเริ่มจากลักษณะใด แต่ประธานกลุ่มสมุนไพรทุกกลุ่มล้วนผ่านการฝึกอบรมจากสถาบันทางการแพทย์ และได้รับใบอนุญาตประกอบโรคศิลปะทั้งสิ้น นอกจากนี้ ยังได้พัฒนาผลิตภัณฑ์ยาชนิดต่าง ๆ อาทิ ลูกประคบ ยาชนิดผง ยาลูกกลอน และยาชนิดแคปซูล ซึ่งทำให้ผลิตภัณฑ์ยาสมุนไพรมีความหลากหลายและสะดวกต่อการรับประทานและการเก็บรักษายิ่งขึ้น ส่วนการถ่ายทอดและการสืบทอดส่วนใหญ่มักเป็นบุคคลในครอบครัว ถ่ายทอดโดยการฝึกปฏิบัติและแนะนำในระหว่างการปฏิบัตินั้น ๆ โดยมีเป้าหมาย 3 ประการ คือ  1) เป้าหมายในการรักษา 2) เป้าหมายทางเศรษฐกิจและการสงเคราะห์ และ 3) เป้าหมายในการอนุรักษ์หลังจากได้รับการถ่ายทอดภูมิปัญญาสมุนไพรแล้ว ผู้สืบทอดมีการปฏิบัติ 3 ด้าน คือ 1) การใช้ภูมิปัญญาสมุนไพรดูแลสุขภาพตนเอง บุคคลใกล้ชิด และคนอื่น ๆ 2) การถ่ายทอดให้บุคคลใกล้ชิด และ 3) การกระตุ้นให้เห็นความสำคัญของสมุนไพรและการอนุรักษ์สมุนไพร Abstract This study aims to examine: the circumstances of the folk wisdom inheritance of health care and benefits of herbs. The population in this study included: (1) doctor of Thai traditional medicine and pharmacy folk wisdom improvement club at M. 4, Ban Nonsrithong, Muang District, Bueng Kan Province, (2) Phu Tok herbal cultivator and transformation group at M. 6, Ban Khamkhanpatthana, Nasang Subdistrict, Sriwilai District, Bueng Kan Province, and (3) Thai wisdom conservationists group at M. 11, Ban Mai Chaiyaphon, Chaiyaphon subdistrict, Muang District, Bueng Kan Province. The simple random sampling method was used, and the participants were selected by purposive sampling method included: herbal philosophers, local pharmacy, 3 heads of herbal groups, herbal group members, and the relatives who are carried on the herbal folk wisdom. The data were collected by the researchers and analyzed by the qualitative data analysis which emphasized on participatory action research (PAR). The research instrument included structured interview adapted from Chaichana (2004). The findings of the present study were as follows: 1. There were 2 types of the folk wisdom inheritance of health care and benefit of using herbs of Bueng Kan herbs group: (1) inherited wisdom from family’s member, (2) training with medical organizations. The first type or the inherited wisdom from family’s member was the factor that has more influent to the number of people who earn a living by herbs. However, the second type or the folk wisdom received from training with medical organizations was the factor that can enhance occupations related to herbs to be acceptable and stable. The results found that, the heads of all herbal groups were trained from medical organization and received Art of Healing Professional license. Besides, several herbal products were improved such as herbal compress, powders, bolus, and capsule which could encourage herbal products to be more diversified and comfortable for taking and maintaining. For the family inherited wisdom, the people in the family were trained by practicing and giving suggestions during activities to complete 3 targets: (1) maintaining target, (2) economic and support target, and (3) conservation target. After receiving inherited herbal folk wisdom, the inheritors could use the knowledge in 3 aspects: (1) use for taking care of themselves, relatives, intimates, and other people, (2) use for inheriting to intimates, (3) use for stimulating the importance of herbs and herbal conservation.